1994
DOI: 10.1152/ajpheart.1994.267.2.h821
|View full text |Cite
|
Sign up to set email alerts
|

Reflex stimulation of cardiac sympathetic nerve activity during static muscle contraction in cats

Abstract: Reflex response of cardiac sympathetic nerve activity (CSNA) during static contraction of the triceps surae muscle was studied using anesthetized cats. A 1-min contraction was evoked by stimulating the peripheral ends of the cut L7 and S1 ventral roots. CSNA increased 48 +/- 13% immediately after the onset of contraction, which was abolished by cutting the L4-S1 dorsal roots. This rapid increase in CSNA preceded rises in heart rate (13 +/- 1 beats/min) and arterial blood pressure (33 +/- 6 mmHg). When tension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
52
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 0 publications
4
52
0
1
Order By: Relevance
“…With respect to the reflex adjustment of the sympathetic nervous system arising from the contracting muscles, static muscle contraction reflexly augments postganglionic sympathetic nerve activities to the heart, kidney, and skeletal muscle within 10 s from the onset of static muscle contraction evoked in anesthetized animals [1][2][3][4]10]. The rapid increase in cardiac sympathetic nerve activity contributes to an acceleration of cardiac rhythm [4], and the increase in renal sympathetic nerve activity contributes to renal vasoconstriction and a reduction in renal blood flow [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the reflex adjustment of the sympathetic nervous system arising from the contracting muscles, static muscle contraction reflexly augments postganglionic sympathetic nerve activities to the heart, kidney, and skeletal muscle within 10 s from the onset of static muscle contraction evoked in anesthetized animals [1][2][3][4]10]. The rapid increase in cardiac sympathetic nerve activity contributes to an acceleration of cardiac rhythm [4], and the increase in renal sympathetic nerve activity contributes to renal vasoconstriction and a reduction in renal blood flow [3].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid increase in cardiac sympathetic nerve activity contributes to an acceleration of cardiac rhythm [4], and the increase in renal sympathetic nerve activity contributes to renal vasoconstriction and a reduction in renal blood flow [3]. The initial cardiovascular responses can be explained by the reflex responses of postganglionic sympathetic nerve activities to the heart and blood vessels as well as a withdrawal of cardiac parasympathetic nerve activity [11], but not by a humoral effect of circulating catecholamines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sympathetic nerve activities (SNA) directed toward blood vessels in a variety of organs including kidney 36,37) , skeletal muscle 38) , and heart 39) , were increased when hindlimb skeletal muscle was continuously and statically contracted in anesthetized or unanesthetized decerebrate cats. Moreover, the roles played by the EPR-evoked sympathoexcitation in mediating renal vasoconstriction 40) and tachycardia 39) have been demonstrated. Of note, skin SNA was not reflexly increased by skeletal muscle contraction 41) , suggesting that the EPR-elicited sympathetic outflows are organ-specific.…”
Section: Exercise Pressor Reflex Arcmentioning
confidence: 99%
“…It was demonstrated in anesthetized cats that the blood pressure was reflexly elevated by passively stretching the triceps surae muscles, which did not generate any muscle metabolites 42) . Subsequent electrophysiological studies demonstrated stimulation of mechanically sensitive group III muscle afferents 43) , cardiac 39) and renal 40) SNA increases, as well as vagal withdrawal 44) , in response to muscle stretch in anesthetized or decerebrate cats. Human subjects also exhibited reflexly increased muscle SNA during passive muscle stretch 45) .…”
Section: Exercise Pressor Reflex Arcmentioning
confidence: 99%